Corticospinal sprouting occurs selectively following dorsal rhizotomy in the macaque monkey - Darian-Smith, Corinna (2013)
The corticospinal tract in the macaque and human forms the major descending pathway involved in volitional hand movements. Following a unilateral cervical dorsal root lesion, where sensory input to the first three digits (D1–D3) is removed, monkeys are initially unable to perform a grasp retrieval task requiring sensory feedback. Over several months, however, they recover much of this capability. Past studies in our lab have identified a number of changes in the afferent circuitry that occur as function returns, but do changes to the efferent pathways also contribute to compensatory recovery? In this study we examined the role of the corticospinal tract in pathway reorganization following a unilateral cervical dorsal rhizotomy. Several months after animals received a lesion, the corticospinal pathways originating in the primary somatosensory and motor cortex were labeled and terminal distribution patterns on the two sides of the cervical cord compared. Tracers were injected only into the region of D1–D3 representation (identified electrophysiologically). We observed a strikingly different terminal labeling pattern post-lesion for projections originating in the somatosensory versus motor cortex. The terminal territory from the somatosensory cortex was significantly smaller compared with the contralateral side (area mean = 0.30 vs 0.55mm(2)), indicating retraction or atrophy of terminals. In contrast, the terminal territory from the motor cortex did not shrink and in 3 of 4 animals, aberrant terminal label was observed in the dorsal horn ipsilateral to the lesion, indicating sprouting. These differences suggest that cortical regions play a different role in post-injury recovery.